MY SAY: Unlocking the 'middle-income trap' - Abd Razak, Dzulkifli (2009)
Over the last three decades, Malaysia has been commended for making successful strides in poverty eradication and enhancing the standard of living. Overall, its growth, aided by impressive infrastructure development, has been considered respectable. As a result, Malaysia is now placed in the upper middle-income economic bracket.